Glyphosate Applied at the Early Reproductive Stage Impairs Seed Production of Glyphosate-Resistant Hairy Fleabane - PIASECKI,C. (2019)
ABSTRACT: Glyphosate-resistant hairy fleabane [Conyza bonariensis (L.) Cronq.] is one of the most important weeds in the world. Among the factors that make this weed species widely distributed in the most diverse environments is the high seed production capacity and dispersal. Hairy fleabane plants not controlled by herbicide application regrowth and overcome crop canopy, use environmental resources, interfere with crops, and complete their life cycle by producing thousands of seeds and replenishing the seed bank. Management strategies that reduce production and viability of hairy fleabane seeds can be adopted within the integrated management to reduce the seed bank and prevent further infestations. In this way, experiments were carried out in a greenhouse and laboratory of seed analysis to evaluate the effect of glyphosate (1,480 g a.e. ha-1) on the production and viability of glyphosate-resistant hairy fleabane seeds when applied at the vegetative and reproductive stages. Seed production was reduced by 68.4 and 100% when glyphosate was applied on hairy fleabane plants at the vegetative and early reproductive stages, respectively, regarding to the control. The viability of hairy fleabane seeds was not influenced by treatments at the evaluated stages. However, glyphosate treatment reduced the hairy fleabane seed production when applied at the vegetative stage . Hairy fleabane seed production is not feasible when glyphosate is applied at the early reproductive stage.